2018
DOI: 10.1002/anie.201810878
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus: Bioactive Nanomaterials with Inherent and Selective Chemotherapeutic Effects

Abstract: Black phosphorus nanosheets (BPs) are demonstrated to be highly bioactive anti‐cancer agents because of their inherent and selective chemotherapeutic effects. Fast intracellular biodegradation of BPs and acute elevation of phosphate anions were observed from different types of cancer cells due to the stronger intracellular oxidative stress and accelerated energy metabolism, but normal cells are not affected. Selective biodegradation of BPs induced G2/M phase arrest and subsequent apoptosis‐ and autophagy‐media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
136
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 52 publications
1
136
0
4
Order By: Relevance
“…Notably, several nanomaterials, such as nanodiamonds and titania‐coated gold nanoparticles, have been demonstrated to be capable of inhibiting autophagy via multiple pathways. A recent report indicates that black phosphorus (BP) nanosheets, which have been explored as robust biodegradable therapeutic platforms in various biomedical settings, could block autophagy flux and aggravate aberrant autophagosomes accumulation . The fast degradation of BP nanosheets in cancer cells as a consequence of intensified reactive oxygen species (ROS) production, promotes the acute elevation of intracellular phosphate anions (PO 4 3− ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, several nanomaterials, such as nanodiamonds and titania‐coated gold nanoparticles, have been demonstrated to be capable of inhibiting autophagy via multiple pathways. A recent report indicates that black phosphorus (BP) nanosheets, which have been explored as robust biodegradable therapeutic platforms in various biomedical settings, could block autophagy flux and aggravate aberrant autophagosomes accumulation . The fast degradation of BP nanosheets in cancer cells as a consequence of intensified reactive oxygen species (ROS) production, promotes the acute elevation of intracellular phosphate anions (PO 4 3− ).…”
Section: Methodsmentioning
confidence: 99%
“…Either elevating 2DG concentrations or prolonging 2DG incubation durations could further aggravate the blockage of lactate production (maximum 77.6% inhibition). Comparatively, BP nanosheets alone failed to elicit distinct inhibitory effect, although at a high BP concentration (64 ppm) the production of lactate from HeLa cells decreased slightly (16.79%), which may result from the intrinsic cytotoxicity of BP . These results demonstrate that 2DG is efficient in restraining glycolysis, while BP nanosheets have minor (or even negligible at low concentrations) antiglycolytic effect.…”
Section: Methodsmentioning
confidence: 99%
“…Mono‐elemental 2D materials such as phosphorene, antimonene, and borophene are particularly promising because of their extraordinary physicochemical properties and outstanding biocompatibility; their electronic and optical properties have resulted in them being regarded as promising anticancer therapeutics . Yu and co‐workers reported that 2D phosphorene could induce significant arrest of the G2/M phase in cancer cells, leading to targeted apoptotic and autophagic cell death with great selectivity . Antimonene‐based photonic drug‐delivery platforms initiated the application of 2D antimonene nanomaterials in cancer theranostics .…”
Section: Introductionmentioning
confidence: 99%
“…The stability of BP@BTA guaranteed to continuously produce 1 O 2 with high efficiency (Figure S11, Supporting Information). Furthermore, the degradation products phosphate anions ensured its nontoxicity and biocompatibility …”
mentioning
confidence: 99%
“…Furthermore, the degradation products phosphate anions ensured its nontoxicity and biocompatibility. [32] Small 2019, 15,1901116 Next, we employed MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assays to estimate biocompatibility of BP@BTA and its effect on Aβ-induced toxicity. PC12 cells without treatment were used as a control.…”
mentioning
confidence: 99%